A case of clitoral Crohn's disease - Soukaina, Sektaoui; Zoubida, Mehsas; Laila, Benzekri; Karima, Senouci (International Journal of Research in Dermatology, 2023)
Crohn's disease (CD) is an inflammatory bowel disease (IBD) that can present with cutaneous lesions, including metastatic lesions. Vulvar CD is a rare manifestation of the disease, with only a few reported cases in the literature. Here we present the case of a 45-year-old woman with metastatic vulvar CD who presented with a one-year history of painful genital swelling. Diagnosis was confirmed through histopathology of the genital lesion. Diagnosis of vulvar CD can be challenging, as the clinical presentation is highly variable. Clinicians should consider the possibility of vulvar CD in patients presenting with aphthous ulcerations, vulvar edema, lymphedema, or lymphangiectasia. Medical treatment options for vulvar CD include corticosteroids, azathioprine, systemic sulfasalazine, cyclosporine, ciprofloxacin, and long-term metronidazole, while surgical interventions include partial or total vulvectomy, laser vaporization, or excision of the lesion. Diagnosis of CD is important, and various diagnostic tools should be used to search for digestive CD. The evolution of vulvar CD can be unpredictable, and surgical intervention may be required when medical treatment fails.